PERAN FINTECH DALAM MENDUKUNG EFISIENSI DAN TRANSPARANSI PASAR MODAL SYARIAH - Nurlisa Safitri; Andi Lisa Aryani Hamjan; Bustan Ramli; Sitti Nikmah Marzuki (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
The development of financial technology (fintech) has had a significant impact on the global financial system, including strengthening the growth of the Islamic capital market in Indonesia. This study aims to analyze how fintech plays a role in increasing the efficiency and transparency of the Islamic capital market while remaining based on Islamic principles. The method used is a qualitative approach through library research, reviewing various literature, scientific journals, and relevant legal documents. The results show that fintech integration contributes to increased efficiency by accelerating transaction processes, reducing operational costs, and expanding investor access to digital financial services. Furthermore, fintech also strengthens the transparency of the Islamic capital market by providing a blockchain-based recording and reporting system that is open, accurate, and verifiable in real time, in line with the values ​​of trust and justice in Islamic transactions. Thus, fintech not only plays a role as a financial technology innovation but also as an instrument for strengthening Islamic values ​​through the application of the principles of honesty, openness, and responsibility in Islamic capital market activities in Indonesia.